P5_12 Killercoaster - Cox, Thomas; Penn Fernandez, Keaton; Mead, Lara; Seagrave, Joshua (Physics Special Topics, 2020)
In this paper we seek to find out whether the world-famous roller coaster, Saw the Ride, at Thorpe Park, could be adapted to kill a human being if the height of its biggest drop were increased. We find that the ride could indeed kill a person if it was high enough, with estimates of 66 m being enough to knock someone unconscious and 89 m potentially being enough to kill a person which is about 3 times higher than the current ride.